(untitled) (Texas Journal of Philology, Culture and History, 2026)
Currently, in the system of higher technical education, teaching the Russian language as an important element of general and professional culture and a means of professional communication has acquired particular relevance. Difficulties in mastering a new (Russian) language are associated with the student’s adaptation to another culture, customs, traditions, history, and values of another people.